Diseño de un sistema de gestión documental de la carrera de Ingeniería Industrial. - Reina Muñoz, Ramiro Aldair (2023)
In the current environment of constant growth of information and documentation, it becomes imperative for organizations to implement efficient document management systems. This thesis focuses on addressing this need by creating a comprehensive system that organizes, categorizes, and manages documents effectively, optimizing the accessibility, security, and reliability of the information. The process begins with the identification of the most relevant classification and categorization criteria. This classification was carried out according to the preliminary institutional evaluation model for the purposes of accreditation of universities and polytechnic schools issued by the Higher Education Quality Assurance Council (CACES). This guarantees that the categories, subcategories and indicators are previously established by a regulatory body such as CACES. The next stage focuses on the design of a document management system which is structured with three main categories: Teaching, Research and Linkage with society, these categories are adapted to the needs identified in the industrial engineering career, within subcategories are structured for each category and within each subcategory we can find indicators established by CACES. This design covers aspects such as the classification, cataloging, indexing, storage and retrieval of documents. Special emphasis was placed on creating a secure and reliable environment for handling documents, guaranteeing the privacy and integrity of the information. The culmination of the project involved the transformation of the document management system into a digital tool using Sharepoint as a tool to be able to design the document management system with the categories, subcategories and indicators identified, where the categories are established as sites within the tool, this tool allows the data to be stored in the cloud to facilitate its recovery. With xvii the right tool, you can access an easy search where you can filter data and stored information, it also allows you to share specific information and provide access to information in a controlled manner. The design of the document management system in the Industrial Engineering career covers several macro results: Improved accessibility because the Sharepoint tool allows a quick search of the stored information, Regulatory compliance because it meets the institutional evaluation requirements for accreditation purposes established by the (CACES).